2021
DOI: 10.3390/diagnostics11020379
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tri-Exponential Decay for Liver Intravoxel Incoherent Motion MRI: A Review of Published Results and Limitations

Abstract: Diffusion weighted imaging (DWI) and intravoxel incoherent motion (IVIM) have been explored to assess liver tumors and diffused liver diseases. IVIM reflects the microscopic translational motions that occur in voxels in magnetic resonance (MR) DWI. In biologic tissues, molecular diffusion of water and microcirculation of blood in the capillary network can be assessed using IVIM DWI. The most commonly applied model to describe the DWI signal is a bi-exponential model, with a slow compartment of diffusion linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 70 publications
(206 reference statements)
1
39
0
Order By: Relevance
“…The clinical implications are less clear in our cohort, as both the bi- and tri-exponential models showed comparable correlations with histopathology. However, NAFLD is known to cause vascular changes 26 , thus particularly the evaluation of the additional perfusion parameter f 2 could be of interest, as this signal originates from larger vessels 11 . We (visually) observed a large decrease in f 2 volumes with increasing levels of fibrosis (Figure 4), which could lead to radiological markers for disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical implications are less clear in our cohort, as both the bi- and tri-exponential models showed comparable correlations with histopathology. However, NAFLD is known to cause vascular changes 26 , thus particularly the evaluation of the additional perfusion parameter f 2 could be of interest, as this signal originates from larger vessels 11 . We (visually) observed a large decrease in f 2 volumes with increasing levels of fibrosis (Figure 4), which could lead to radiological markers for disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…For healthy volunteers, an overview of average tri-exponential IVIM-values was published in a recent review 11 . Values for ‫ܦ‬ ranged between 0.98-1.35 *10 -3 mm 2 /s which is in line with what we found with the IVIM 3 -NET and higher than our tri-exponential LSQ fit as seen in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent review suggested MRE had a summary AUC, sensitivity and specificity for diagnosing stage ≥F1 of 0.87, 71%, 85%, respectively (12). It is possible that additional approaches such as a combination all of all diffusion metrics and removal of b-value=0 s/mm 2 data from IVIM modeling can further improve the results of Troelstra et al As starting from b=0 image, the relationship between liver DWI signal and b-value does not follow bi-exponential decay (2,26), in our experience, removal of b-value=0 s/mm 2 data from IVIM modeling greatly improves the diagnostic performance of resulted IVIM parameters (2,9). The fact that slow diffusion measure and fast slow diffusion measures are mutually constrained further increases the necessity of checking all IVIM parameters together (instead of evaluating these parameters individually) (7,27).…”
mentioning
confidence: 99%
“…Recent advances in MRI technology have made it possible to acquire not only morphological information, but also functional information even in MR equipment of clinical use. In terms of hepatic functional information, diffusion and perfusion parameters such as apparent diffusion coefficient (ADC) measurement, bi‐exponential intravoxel incoherent motion (IVIM), 1 and tri‐exponential IVIM 2 technique are getting used in clinical analyses of liver disease. IVIM is first established by Le Bihan, 1 which is used as a quantitative parameter of diffusion and perfusion of water molecules.…”
mentioning
confidence: 99%